(untitled) (Journal of Universal Science Research, 2024)
This article discusses route planning for a mobile robot in three-dimensional space using the Probabilistic Roadmap (PRM) algorithm. The mathematical apparatus of PRM allows you to build a state graph for the robot’s movement space, taking into account obstacles and environmental features. The developed Python program includes an implementation of the PRM algorithm to find the optimal path in 3D space. Experiments on route generation in various environments were conducted to demonstrate the effectiveness and accuracy of the proposed approach. The results obtained confirm the applicability of the PRM algorithm for route planning of mobile robots in complex 3D environments.